1988
DOI: 10.1159/000261119
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lycasin® versus Sucrose Sweets in Demineralization Studies of Human Enamel and Hydroxylapatite

Abstract: Boiled sweets formulated with Lycasin® were compared with conventional sugar-base sweets. Incubated in media containing solutions of the sweets, mixed cultures of oral microorganisms produced less polysaccharide and acid, with significantly less demineralizing action on dental enamel and hydroxylapatite, from the Lycasin than from the sugar-base products. In comparison with these differences, the effects of changing the flavouring acid combinations in the sweets were minor, but levels of citric and malic acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…In some recent studies on juices, the total titratable acidity levels (equivalence to 0,05M NaOH) were blackcurrant (73) >>raspberry (44) >rosehip, orange and strawberry (all approx. equal at [26][27][28] >apple (20) (unpublished observations). There is some evidence that this approach has been used to make sure that the acidity of infants' fruit drinks is low, keeping the levels of demineralization significantly lower than those from a selection of adults' fruit drinks (21).…”
Section: The Addition Of Citrate To Drinksmentioning
confidence: 99%
“…In some recent studies on juices, the total titratable acidity levels (equivalence to 0,05M NaOH) were blackcurrant (73) >>raspberry (44) >rosehip, orange and strawberry (all approx. equal at [26][27][28] >apple (20) (unpublished observations). There is some evidence that this approach has been used to make sure that the acidity of infants' fruit drinks is low, keeping the levels of demineralization significantly lower than those from a selection of adults' fruit drinks (21).…”
Section: The Addition Of Citrate To Drinksmentioning
confidence: 99%
“…Isomalt and maltitol syrups are widely used to replace sucrose in confectionery because of their cariostatic and hypocaloric properties compared to sucrose (Grenby & Saldanha, 1988;Ziesenitz & Siebert, 1987). These polyol sugars have excellent organoleptic, technological and physicochemical properties, making them ideal for formulation into 'toothfriendly', 'reduced calorie' and or 'sugar-free' products suitable for both adults and children (Zumbé et al, , 2001Sicard & Le Bot, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…There are fewer options for replacing sugar in solid products than in liquid medicines suitable bulk sweeteners is limited, and the polyols have a number of disadvantages. The Lycasins have better dental properties than sugars (4- 7), so these were the materials chosen for makmg the lozenges which were evaluated in the studies reported here.…”
Section: Introductionmentioning
confidence: 99%